Proceedings of the International Conference for High Performance Computing, Networking, Storage and Analysis 2019
DOI: 10.1145/3295500.3356176
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale study of MPI usage in open-source HPC applications

Abstract: Understanding the state-of-the-practice in MPI usage is paramount for many aspects of supercomputing, including optimizing the communication of HPC applications and informing standardization bodies and HPC systems procurements regarding the most important MPI features. Unfortunately, no previous study has characterized the use of MPI on applications at a signicant scale; previous surveys focus either on small data samples or on MPI jobs of specic HPC centers. This paper presents the rst comprehensive study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 10 publications
1
27
0
1
Order By: Relevance
“…These constructs are typical of non-deterministic application's communication patterns, as presented in [1], [2], [7]. Furthermore, characterization of trends in how HPC applications use MPI features presented in [8] proves that the majority of MPI applications with nondeterministic patterns use point-to-point communication constructs, guaranteeing the broader impact of our framework across scientific domains. Thus, the value proposition of our work is that, supported by our framework, scientists can ultimately bootstrap their process for diagnosing nondeterministic bugs or addressing reproducibility failures reducing the labor-intensive manual inspection of complex code.…”
mentioning
confidence: 79%
“…These constructs are typical of non-deterministic application's communication patterns, as presented in [1], [2], [7]. Furthermore, characterization of trends in how HPC applications use MPI features presented in [8] proves that the majority of MPI applications with nondeterministic patterns use point-to-point communication constructs, guaranteeing the broader impact of our framework across scientific domains. Thus, the value proposition of our work is that, supported by our framework, scientists can ultimately bootstrap their process for diagnosing nondeterministic bugs or addressing reproducibility failures reducing the labor-intensive manual inspection of complex code.…”
mentioning
confidence: 79%
“…A recent study of about 100 MPI applications [24] has shown, that most codes require MPI-2 or lower and point-topoint communication and collectives are the majority of used MPI features. However, derived MPI datatypes are the fourth most used feature in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that some features are irrelevant to some errors (e.g., RMA operations cannot produce a Request Lifecycle error). It may be observed that all MPI features are represented in the benchmark with a predominance of basic collectives and point-to-point operations which correspond to the most used features in HPC applications [30].…”
Section: B Features and Errors Coveragementioning
confidence: 99%